Overexpression of NOX2 Exacerbates AngII-Mediated Cardiac Dysfunction and Metabolic Remodelling - Synne S. Hansen; Tina M. Pedersen; Julie Marin; Neoma T. Boardman; Ajay M. Shah; Ellen Aasum; Anne D. Hafstad (MDPI AG, 2022)
The present study aimed to examine the effects of low doses of angiotensin II (AngII) on cardiac function, myocardial substrate utilization, energetics, and mitochondrial function in C57Bl/6J mice and in a transgenic mouse model with cardiomyocyte specific upregulation of NOX2 (csNOX2 TG). Mice were treated with saline (sham), 50 or 400 ng/kg/min of AngII (AngII50 and AngII400) for two weeks. In vivo blood pressure and cardiac function were measured using plethysmography and echocardiography, respectively. Ex vivo cardiac function, mechanical efficiency, and myocardial substrate utilization were assessed in isolated perfused working hearts, and mitochondrial function was measured in left ventricular homogenates. AngII50 caused reduced mechanical efficiency despite having no effect on cardiac hypertrophy, function, or substrate utilization. AngII400 slightly increased systemic blood pressure and induced cardiac hypertrophy with no effect on cardiac function, efficiency, or substrate utilization. In csNOX2 TG mice, AngII400 induced cardiac hypertrophy and in vivo cardiac dysfunction. This was associated with a switch towards increased myocardial glucose oxidation and impaired mitochondrial oxygen consumption rates. Low doses of AngII may transiently impair cardiac efficiency, preceding the development of hypertrophy induced at higher doses. NOX2 overexpression exacerbates the AngII -induced pathology, with cardiac dysfunction and myocardial metabolic remodelling.